THE STUDENT SCIENCE: ACHIEVEMENT AND PERSPECTIVES - Andrey A. Baranov; Viktor N. Malashenko; Olga V. Klimacheva; Olga I. Khmel’Tsova (Высшее образование в России)
The article presents the basic stages of the history, modern stage, sections of scientific students’ work, achievements and thebasic perspective directions ofstudents’ science development at the Yaroslavl State Medical Academy. The Students’ Scientific Society of the Academy now includes 50 research circles and involves about 800 students.